2021
DOI: 10.1177/15459683211048771
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cortisol Profile Associations With Cognitive Impairment After Severe Traumatic Brain Injury

Abstract: Background Cognitive impairments commonly occur after traumatic brain injury (TBI) and affect daily functioning. Cortisol levels, which are elevated during acute hospitalization for most individuals after severe TBI, can influence cognition, but this association has not been studied previously in TBI. Objective We hypothesized that serum and cerebral spinal fluid (CSF) cortisol trajectories over days 0–5 post-injury are associated with cognition 6-month post-injury. Methods We examined 94 participants with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Our results supported the idea that the interaction of AD genetic factors with mTBI leads to brain atrophy in AD‐vulnerable regions 5 . Regarding the neuropsychological signature, early lvPPA‐AD is characterized by a decline in language fluency, 36,43 which is one of the neuropsychological complaints of patients with mTBI as well 15,16 . In addition, we found that the atrophy in GM, rather than the WM, within the left superior and middle temporal gyri could predict the decline in language fluency for mTBI APOE ε4 allele carriers.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our results supported the idea that the interaction of AD genetic factors with mTBI leads to brain atrophy in AD‐vulnerable regions 5 . Regarding the neuropsychological signature, early lvPPA‐AD is characterized by a decline in language fluency, 36,43 which is one of the neuropsychological complaints of patients with mTBI as well 15,16 . In addition, we found that the atrophy in GM, rather than the WM, within the left superior and middle temporal gyri could predict the decline in language fluency for mTBI APOE ε4 allele carriers.…”
Section: Discussionsupporting
confidence: 86%
“…5 Regarding the neuropsychological signature, early lvPPA-AD is characterized by a decline in language fluency, 36,43 which is one of the neuropsychological complaints of patients with mTBI as well. 15,16 In addition, we found that the atrophy in GM, rather than the WM, within the left superior and middle temporal gyri could predict the decline in language fluency for mTBI APOE ε4 allele carriers. The longitudinal registration of pairs of T1 images was based on alignment between the first and second scans of each participant, in which a linear transform may be mostly influenced by the GM rather than the WM.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…While HPA axis hypoactivity is potentially dangerous, sustained hyperactivity can also lead to allostatic loading and poorer outcomes. High circulating cortisol that did not decline in the first five days after severe injury predicted poorer cognitive and overall outcomes at 6 months ( Barton et al, 2021 ; Santarsieri et al, 2014 ) although it remains unclear whether the acutely elevated glucocorticoids are imperiling recovery per se or are indicative of greater tissue damage. Thus, as predicted by allostatic theory, optimal recovery seems to occur in conditions when the HPA axis can produce sufficient physiological levels of activation but in a relatively time-limited manner.…”
Section: Traumatic Brain Injury Allostasis and Allostatic Loadmentioning
confidence: 99%